Hungarian Monitoring, 19 October 1988 . [Magyar rádiófigyelő], 1988. október 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Personnel changes in the League of Communists of Yugoslavia - Disarmament questions in Iranian-American relations - Do the Polish government and measured opposition's reform ideas resemble each other? - American missile disarmament - Role of Soviet scientists in perestroika Domestic Affairs: - Romanian National Peace Committee rejects Hungarian Peace Committee's invitation citing heavy domestic political schedule - Head priest of Romanian Orthodox church: Hungarian-Romanian relations should not be discussed at Christians' Peace Conference - "Many people today express statements critical of the Party": series of political debates at Hungarian Socialist Workers' Party (MSZMP) Political College starts today - "Hungary is fundamentally interested in pan-European disarmament": Gyula Horn at UN General Assembly first committee - What will the Party's role be in a company that becomes partly or wholly American owned? - Warsaw Pact military exercises Economy: - Meeting of government and Chamber of Commerce representatives - Agreement on Hungarian-American agricultural cooperation - Hungarian experts trained in America - National Association of Entrepreneurs (VOSZ) presidency meeting - Skála stock company Külpolitika: - Személyi változások a JKSZ-ben - Leszerelési kérdések és az iráni-amerikai kapcsolatok - Hasonlítanak-e egymásra a lengyel kormány és a mérsékelt ellenzék reformelképzelései? - Az amerikai rakéta leszerelés - A szovjet tudósok szerepe a peresztrojkában Belpolitika: - A Román Országos Békebizottság sűrű belpolitikai programjára hivatkozva visszautasította a Magyar Béketanács meghívását - A román ortodox egyház egyik főpapja szerint nem szabad szóba hozni a magyar-román viszályt a Keresztyén Békekonferencián - "A pártról ma elég sokan elítélőleg nyilatkoznak"… Politikai vitasorozat kezdődött ma az MSZMP Politikai Főiskoláján - "Magyarország alapvetően érdekelt az összeurópai leszerelésben" - Mondta HORN Gyula az ENSZ-közgyűlés főbizottságában - Mi lesz a párt sorsa például egy olyan cégnél, amely részben, vagy egészében amerikai tulajdonba kerül? - VSZ hadgyakorlat Gazdaság: - A kormány és a Gazdasági Kamara képviselőinek találkozója - Megállapodás született a magyar-amerikai mezőgazdasági együttműködésről - Magyar szakembereket képeznek Amerikában - VOSZ elnökségi ülés - A Skála Rt